2012
DOI: 10.1111/j.1447-0756.2012.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen concentrate substitution therapy for obstetric hemorrhage complicated by coagulopathy

Abstract: Fibrinogen concentrate substitution therapy for obstetric hemorrhage increases fibrinogen levels and appears to be effective in managing dilutional or consumptive coagulopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…Although a few case series have been reported previously17, there are no controlled studies of the efficacy and complications of fibrinogen concentrate usage in patients with massive obstetric haemorrhage and hypofibrinogenaemia9101112131415. Only one study included a control group; however, this study compared the use of cryoprecipitate and fibrinogen concentrate rather that comparing the use and non-use of fibrinogen concentrate18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few case series have been reported previously17, there are no controlled studies of the efficacy and complications of fibrinogen concentrate usage in patients with massive obstetric haemorrhage and hypofibrinogenaemia9101112131415. Only one study included a control group; however, this study compared the use of cryoprecipitate and fibrinogen concentrate rather that comparing the use and non-use of fibrinogen concentrate18.…”
Section: Discussionmentioning
confidence: 99%
“…The use of fibrinogen and other coagulation factor concentrates that include high levels of fibrinogen should therefore provide therapeutic benefits by efficiently restoring the levels of key coagulation factors. However, there are few studies comparing the efficacy of these blood products in obstetric patients with that of a relevant control group91011121314, and no reports have investigated this in a controlled clinical setting in individuals with hypofibrinogenaemia15 because these are generally emergency medicine patients. Therefore, in the present study we retrospectively compared the effects of administering a fibrinogen concentrate to patients treated for hypofibrinogenaemia (fibrinogen < 150 mg/dl) attributable to massive obstetric haemorrhage with those observed in patients treated with FFP alone, including reduced complications.…”
mentioning
confidence: 99%
“…Coagulopathy was categorized as dilutional or consumptive, depending on the cause of hypofibrinogenemia. Causes of dilutional coagulopathy, which is evoked by massive infusion and transfusion, resulting in coagulation factor deficiency, included uterine atony, genital tract trauma and uterine inversion, whereas, those of consumptive coagulopathy, in which breakdown of cross‐linked fibrin and augmented fibrinolysis may enhance the consumption of coagulation factors at the decidua of placental attachment, included placental abruption …”
Section: Methodsmentioning
confidence: 99%
“…They reported that fibrinogen levels significantly increased after fibrinogen substitution therapy [19]. According to Casini et al [20], the following formula should be used to evaluate the amount of fibrinogen to be administered = (target fibrinogen level [g/L] -basal fibrinogen level) 9 0.043 9 ??…”
Section: Discussionmentioning
confidence: 99%